Data Flow Diagrams of an Electronic Medical Record System in Mansoura Hospital (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper develops an Electronic Medical Record System in the Neurosurgical Unit of Mansoura General Hospital using Data Flow Diagrams. Data Flow Diagrams are the first step to design the system blueprint as they represent users requirements. The paper creates a context-aware fisheye view as it is more successfully communicate the information contained in a set of Data Flow Diagrams (DFD) than a traditional context-free presentation. A case study and experimental results show that our context-aware fisheye DFD's are well suited for application in developing Electronic Medical Record System. This makes the expert system more reliable and faster response